Níveis de eficiência de mercados internacionais através da precificação de ações de empresas do setor de seguros - Gomes, Kátia Teresinha Guerra (2012)
This dissertation aims at the study of 22 companies of the international insurance segment in order to ascertain whether insurers already consider in the price of its shares the expectations of future crises and also analyze which insurance market is more efficient. To this purpose, this work studied and presented results on the following aspects: a study of 20 companies of highest market value of the international insurance segment, verifying the performance of rolling stock of each comparing with the market index of the stock exchange on which the action is negotiated. Additionally, conducted an analysis between the Brazilian insurance markets and other markets studied in the sample, verifying if the insurance segment in Brazil presents itself more efficient than international markets surveyed; and third, and last, an analysis of the stock indexes out of reshaping crisis moments as selected sample. For this survey, the methodology which has been used was the study of events. According to the results observed in this work and except that the findings are limited to the sample observed, the results indicate the occurrence of the generation of statistically significant abnormal returns after the announcement of the crisis. For the windows immediately before and after the event window, was not observed to generate statistically significant abnormal returns. Thus, we accepted the null hypothesis, assuming indications anticipated adjustments, resulting from an accumulation of factors. The results comparison among companies of the 4 sub samples showed the absence of a default behavior for the series as a whole. And considering that economic crises are the result of continuous systemic adverse events, with the results published in the media, it is reasonable to accept that the prices gradually adjusted before the measurement point